Hambatan Belajar Siswa Kelas XI SMA pada Materi Persamaan Trigonometri - Oktavihari, Dita; Priatna, Nanang; Avip Priatna, Bambang (FKIP Universitas Mataram, 2024)
This study aims to identify learning barriers experienced by students in trigonometric equation material. The type of research used is qualitative research with a phenomenological approach. The subjects of this study were 36 students of class XI SMAN 5 Mataram. Data collection used were tests, observations, interviews, and document studies. The data analysis technique used is according to Miles and Huberman consisting of data reduction, data presentation, and conclusion. The results obtained are that students experience ontogenic, epistemological, and didactic learning barriers. Instrumental ontogenic barriers, namely students are still hampered by key things in trigonometric equation material, students do not understand the meaning of k well in the trigonometric equation formula. Epistemological barriers, namely, students are constrained by prerequisite material, and students also experience limited context in solving the questions given. Didactic barriers are that students only follow what has been taught by the teacher during the learning process. This study can be a basis for making didactic designs so that learning can occur according to the objectives.